2013
DOI: 10.1007/s00330-013-2842-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of malignant and benign pulmonary nodules with first-pass dual-input perfusion CT

Abstract: • Modern CT equipment offers assessment of vascular parameters of solitary pulmonary nodules (SPNs) • Dual vascular supply was investigated to differentiate malignant from benign SPNs. • Different dual vascular supply patterns were found in malignant and benign SPNs. • The perfusion index is a useful biomarker for differentiate malignancy from benignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 16 publications
2
40
0
1
Order By: Relevance
“…16 Consistent with the results of the recent study by Yuan et al, 22 our findings show that, in NSCLC, the bronchial contribution is higher than the pulmonary contribution. In addition, we have now demonstrated that there are also differences depending on the NSCLC subtype: LCC shows higher bronchial and pulmonary BV and BF compared with AC and SCC.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…16 Consistent with the results of the recent study by Yuan et al, 22 our findings show that, in NSCLC, the bronchial contribution is higher than the pulmonary contribution. In addition, we have now demonstrated that there are also differences depending on the NSCLC subtype: LCC shows higher bronchial and pulmonary BV and BF compared with AC and SCC.…”
Section: Discussionsupporting
confidence: 83%
“…20 Cutoff values have been defined for several CTP parameters to differentiate benign from malignant pulmonary nodules, with lower perfusion index (PI) and higher BF and BV obtained in malignancy. 21,22 Similar accuracy of CTP and fluoro-2-deoxy-D-glucose-PET/CT was confirmed in the meta-analysis by Cronin et al 23 Several studies have addressed differences of CTP parameters among histological lung cancer subtypes, assessing them with a single-input CTP analysis of either the pulmonary or the bronchial arterial system. [24][25][26][27] Computed tomography perfusion in lung cancer remains a technical challenge, particularly due to breathing motion over time.…”
Section: Results: According To Biopsy 37 Patients Had Nsclc (22 Adenmentioning
confidence: 82%
See 1 more Smart Citation
“…Using global mean or median values can also work for diagnosis purposes, where CTp has been used to discriminate between benign and malignant in different types of lung lesions, including pulmonary solitary nodules. For instance, the overall mean of pulmonary index, pulmonary and bronchial blood flow (BF), is computed on multiple slices in [29] and on three tumour sections chosen according to the axial, coronal, and sagittal planes, in [30]. The overall median of all the CTp parameters for the whole tumour is computed in [14], where the median was preferred over the mean operator to avoid outliers.…”
Section: Introductionmentioning
confidence: 99%
“…The absolut BF, BV, MTT and TTP were commonly evaluated for tumor identify. In mostly past researches [9,10,15,16] , many different types of parotid tumor were usually contained as benign group to compared to malignant lesiones. So far, few studies evaluated the distinction of various histological types of benign tumors by comparing perfusion parmaters.…”
Section: Pei (Hu)mentioning
confidence: 99%